Risk Factors for Incidence of Intrauterine Fetal Distress in Hospital of Pamekasan - Mochamad Ma'roef (Universitas Muhammadiyah Malang, 2021)
Fetal distress during intrauterine is related to many factors. Knowing the risk factors will provide an effort to prevent and detect early fetal distress cases. The objective was to determine the risk factors for fetal distress during intrauterine treatment at dr. H. Slamet Martodirdjo Pamekasan. The method used is analytic observational with a cross-sectional method and the sample is simple random sampling. Samples taken were 184 patients in the delivery room dr. H. Slamet Martodirdjo general hospital Pamekasan. Data was taken by observation from patient medical records during 2018. Through this study, 92 patients experienced intrauterine fetal distress. The main risk factors for fetal distress was umbilical cord twists (p: 0.003, OR: 6,857, 95% CI: 1,914-24,572) and protective factors were maternal anemia (p: 0.018, OR: 0.141, 95% CI : 0.028-0.714). There are several risk factors for fetal distress during the intrauterine process at dr. H. Slamet Martodirdjo Pamekasan, the main factor was umbilical cord twisting where pregnant women with umbilical cord twists have a 6 times risk of experiencing fetal distress compared to those who do not.